Dying and multiplying life - Rodríguez-Arias, David (The Hastings Center report, 2014)
It was only after James P. Lovette's death, in 2006, that I discovered that the twenty-four-year-old colleague and friend with whom I had spent so many afternoons debating issues in organ transplantation had been the first successful child heart transplantee in the world and one of the longest-living survivors of a second transplant. During the years we met, he never even hinted at the fact that three different hearts had beaten in his chest. The revelation that his life had been an almost uninterrupted chain of medical challenges suddenly made me appreciate his quirkiness in a whole new light. Organ transplantation crudely exemplifies a traditional moral dilemma between means and ends: in order to save a life, someone else has to die. Bioethicists involved in this field have the role of identifying the ethical issues surrounding organ donation and helping others to argue in an intelligible and convincing way. In my view, bioethicists have the obligation to foster a discussion as open and transparent as possible on these matters. Still, I sometimes fear that I may be helping to cause unnecessary harms to potential recipients who are desperately waiting for a vital organ. Scholars would be chillingly cold if their quest for truth systematically came at the cost of lives lost. Every life can be meaningful and provide meaning to many others. This is true even with organ recipients, who often have short lives full of considerable suffering.